Understanding Impulse Buying in Online Shopping: A Systematic Review of Behavioral Drivers and Consumer Decision Mechanisms - Ika Tirta Candra Rini; Budi Astuti (Jurnal Ekuisci, 2026)
Background. The rapid expansion of digital commerce ecosystems has significantly transformed consumer purchasing behavior and intensified the prevalence of impulse buying in online shopping environments. Existing studies have examined various antecedents of online impulse buying behavior, including emotional arousal, shopping enjoyment, trust, social influence, hedonic value, and cognitive factors. However, the current literature remains theoretically fragmented and predominantly variable-centered, resulting in limited integrative understanding regarding how behavioral and psychological drivers collectively shape consumer decision mechanisms in digitally mediated shopping contexts. Aims. Accordingly, this study aims to develop a more integrative understanding of online impulse buying behavior through a systematic literature review approach. Methods. This study employed a Systematic Literature Review (SLR) method following a PRISMA-oriented procedure. Literature retrieval was conducted in Scopus via Publish or Perish using the search keywords (“impulse buying” OR “impulsive buying”) AND (“online shopping” OR “e-commerce” OR “digital commerce”). The initial search identified 200 articles; 135 met the inclusion and eligibility criteria and were included in the final review. The selected studies were analyzed using a thematic synthesis approach to identify dominant theoretical perspectives, behavioral drivers, consumer decision-making mechanisms, and emerging research gaps in the online impulse buying literature. Result. The findings reveal that online impulse buying behavior should no longer be understood merely as spontaneous purchasing behavior driven by emotional urgency. Instead, the reviewed literature indicates that online impulse buying reflects a digitally mediated behavioral architecture that emerges from the interaction among emotional stimulation, cognitive simplification, socially mediated influence, and gratification-oriented shopping values. The review further demonstrates that the existing literature remains fragmented and heavily focused on isolated antecedents, thereby limiting broader conceptual understanding of the interactions among behavioral mechanisms underlying online impulse buying. Conclusion. This study contributes to the online consumer behavior literature by offering an integrative synthesis of the behavioral and psychological mechanisms underlying online impulse buying. Implementation. The review also advances a broader conceptual understanding of digitally mediated consumer decision-making processes and highlights future research opportunities concerning emerging digital commerce technologies and ethically responsible online shopping environments.